2021
DOI: 10.3389/fmed.2021.678438
|View full text |Cite
|
Sign up to set email alerts
|

Development and Functional Characterization of Fetal Lung Organoids

Abstract: Preterm infants frequently suffer from pulmonary complications due to a physiological and structural lung immaturity resulting in significant morbidity and mortality. Novel in vitro and in vivo models are required to study the underlying mechanisms of late lung maturation and to facilitate the development of new therapeutic strategies. Organoids recapitulate essential aspects of structural organization and possibly organ function, and can be used to model developmental and disease processes. We aimed at genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In the past decade, significant advances have been achieved in understanding the molecular and cellular mechanisms of tissue repair and regeneration with the advent of stem/progenitor cell-based organoid technologies 32 . Regarding lung organoid studies, 2D ALI and 3D organoid models of lung epithelial stem/progenitor cells are widely used due to their multidimensional niche, which mimics the morphological and cellular compositions of the airway epithelium in vivo 35 . In our study, 2D and 3D organotypic models using mouse LSPCs were successfully established, based on the results of morphological analyses ( Figures S1 -S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, significant advances have been achieved in understanding the molecular and cellular mechanisms of tissue repair and regeneration with the advent of stem/progenitor cell-based organoid technologies 32 . Regarding lung organoid studies, 2D ALI and 3D organoid models of lung epithelial stem/progenitor cells are widely used due to their multidimensional niche, which mimics the morphological and cellular compositions of the airway epithelium in vivo 35 . In our study, 2D and 3D organotypic models using mouse LSPCs were successfully established, based on the results of morphological analyses ( Figures S1 -S3).…”
Section: Discussionmentioning
confidence: 99%
“…They simulate the morphogenesis, structures and functions of the respiratory system in vivo , providing a versatile and reliable in vitro culture system to study lung development and regenerative medicine, model diseases and screen drugs 32 , 33 . During the past decade, lung organotypic models, including 2D air-liquid interface (ALI) and 3D organoid cultures, have become remarkable platforms to investigate the differentiation and repair of LSPCs, morphogenesis and function of ciliated epithelium, as well as mucus production and airway clearance 34 , 35 . Recently, important advances in illustrating the mechanisms of COVID-19 have been reported using organoid platforms 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of organoids to model lung development and diseases has gained significant attention recently [87][88][89]. Currently, lung organoids are usually constructed from primary tissue, lung progenitors, or induced pluripotent stem cells (iPSCs) in specific 3D culture conditions [87][88][89][90][91]. The common methods for isolating primary AT2 cells for organoid culture are using FACS or MACS with a unique antibody, and the generation of 3D organoids usually requires the use of a cell support that mimics it the physiological environment from mesenchymal cells, endothelial cells, and/or Pdgfra + fibroblasts [8,92,93].…”
Section: Discussionmentioning
confidence: 99%
“… 50 demonstrated exogenous FGF signals play roles in driving de novo fetal pulmonary alveolar morphogenesis. Rodent lung organoids derived from earlier pseudoglandular 82 or later alveolar 83 lung tissues have also been developed for normal lung development studies. To determine whether human lung develops in a similar way as mouse lung does, Nikolic et al.…”
Section: Fetal Tissue–derived Organoids In Fetal Organ Development Re...mentioning
confidence: 99%
“…Employing fetal pulmonary organoids derived from E17.5 fetal mouse lung, Mondrinos et al 50 demonstrated exogenous FGF signals play roles in driving de novo fetal pulmonary alveolar morphogenesis. Rodent lung organoids derived from earlier pseudoglandular 82 or later alveolar 83 lung tissues have also been developed for normal lung development studies. To determine whether human lung develops in a similar way as mouse lung does, Nikolic et al 51 developed a long-term renewable human tip organoid derived from human GW 5-9 lungs and captured differentiative behavior of tips toward bronchiolar or alveolar lineages in vitro.…”
Section: Lungmentioning
confidence: 99%